Mushroom polysaccharides from Grifola frondosa (Dicks.) Gray and Inonotus obliquus (Fr.) Pilat ameliorated dextran sulfate sodium-induced colitis in mice by global modulation of systemic metabolism and the gut microbiota - Sun, Runbin; Jin, Dandan; Fei, Fei; Xu, Zhi; Cao, Bei; Li, Juan (Frontiers in Pharmacology, 2023)
Polysaccharides from Grifola frondosa (Dicks.) Gray (HSH) and Inonotus obliquus (Fr.) Pilat (BHR) showed noticeable effects on dextran sulfate sodium (DSS)-induced colitis, but their systemic modulation effects have not been fully revealed. This study aimed to investigate the regulation of the gut microbiota and systemic metabolism by HSH and BHR in DSS-induced colitis. C57BL/6J mice were given DSS (2.5%) in water and were treated with HSH and BHR (200 mg/kg/day) by gavage. Body weight and colon length were recorded, and H&E and AB-PAS staining of the colon were conducted to evaluate the model and the protective effect of the polysaccharides. Additionally, an LC-QTOF/MS-based untargeted metabolomic platform was used to identify the metabolites in the serum, colon tissue, gut contents, and faeces and investigate differential metabolites and metabolic pathways. 16S rDNA gene sequencing was used to measure the composition of bacterial communities. The results showed that the mouse colitis model was established successfully, as evidenced by an increased disease activity index score (2.83 ± 0.62 vs. 0.06 ± 0.14 (P < 0.001)) and shortened colon length (5.43 ± 0.64 cm vs. 7.04 ± 0.29 cm (P < 0.001)), and HSH and BHR ameliorated DSS-induced colitis by improving the disease activity index (2.17 ± 0.28 and 1.83 ± 0.29, respectively) and restoring the colon length (6.12 ± 0.30 cm and 6.62 ± 0.35 cm, respectively). HSH and BHR significantly modulated metabolites involved in aromatic amino acid metabolism, the citrate cycle, purine metabolism, pyrimidine metabolism, etc. HSH and BHR increased the Chao1 index by 64.25% and 60.25%, respectively, and they increased the Shannon index by 13.02% and 10.23%, respectively. They both reversed the increase in the abundances of g_Odoribacter, g_Clostridium, g_AF12, g_Parabacteroides and g_Turicibacter and reversed the decrease in the abundance of g_unclassified_Bacteria induced by DSS. Specifically, HSH reversed the reductions in g_unclassified_Lactobacillales and g_Ruminococcus, and BHR reversed the decreases in g_unidentified_Coriobacteriaceae and g_unclassified_Firmicutes. These results suggested that HSH and BHR may ameliorate DSS-induced colitis by global modulation of systemic metabolism and the gut microbiota. Targeting the gut microbiota may be a potentially effective strategy to modulate systemic metabolism and treat colitis.